IMPLEMENTATION OF FACE SIMILARITY USING TINY FACE DETECTOR - Mohammad Kasyful Anwar; Diky Firdaus (IJISCS (International Journal of Information System and Computer Science), 2020)
The development of cloud technology and Software As A Services (SaaS) applications is happening very expeditiously. Many applications are currently used by users using cloud technology, including the Human Resources (HR) application. The problem arising from cloud-based HR applications is regarding the issue of validity, especially when doing attendance so that it cannot be entrusted or represented by others. In this paper, it is explained how to maintain the validity of attendance in cloud-based HR applications by looking at the level of face similarity using tiny face detector.